Dynamic Causality Between Stock Return and Exchange Rate: Is Stock-Oriented Hypothesis More Relevant in Malaysia? - Lau, Wee Yeap; Go, You How (Springer, 2018)
In the aftermath of Lehman shock, the effect of quantitative easing policy swiftly permeated the emerging stock markets, causing substantial fluctuation in currency value of different countries. This study aims to determine whether short-term capital flow is more relevant than trade balance in affecting the exchange rate or vice versa by examining the dynamic relationship between stock return and change of Malaysian Ringgit to US Dollar (MYRUSD) as well as between stock return and change of Malaysian Ringgit to Chinese Yuan (MYRCNY). Based on daily data of July 2005–July 2015, our results show: First, in the pre-crisis period, stock returns are found to Granger cause MYRCNY and MYRUSD in mean and variance. Second, during the crisis, the causality from stock returns to MYRCNY and MYRUSD is only found in the mean. Third, in the post-crisis period, there is causality-in-mean from stock returns to MYRUSD, in addition to volatility spillover from stock returns to both MYRCNY and MYRUSD. Hence, it can be concluded that the stock-oriented hypothesis is more tenable in Malaysia, suggesting that MYRUSD is determined by the short-term capital flow. Furthermore, the forex market is informational inefficient during the post-crisis period when the stock return has predictive power over the exchange rate.